The Measuring Development Impact with the Social Return on Investment Approach Model - Efri Syamsul Bahri; Hendro Wibowo; Achmad Ichsan Nusapati (International Journal of Management Science and Application, 2024)
Development has a strategic role in improving community welfare. Development covers the social, economic and environmental fields. Development can be called successful when it significantly impacts various stakeholders. This research uses the Social Return on Investment (SROI) approach model to describe impact measurement. This research uses qualitative methods with a descriptive approach and a literature study. The results of this research show that the impact of development can be measured using the SROI model. Based on the SROI model, measuring development impacts includes three dimensions: social, economic and environmental. Implementing impact measurement is a form of accountability and transparency in development. Therefore, to get an idea of the magnitude of the impact, development in various sectors needs to be measured using the SROI model. Government and non-government organizations can use the SROI model to measure the impact of development that will and has been carried out.